Increasing Growth and Yield of Shallot Using Nano Zeolite and Nano Crab Shell Encapsulated NK Fertilizer in Entisols and Inceptisols - Ratih Kumalasari; Eko Hanuddin; Makruf Nurudin (Department of Agrotechnology, Universitas Muhammadiyah Yogyakarta, 2022)
Nanotechnology can be used to produce slow-release fertilizers. Zeolite and crab shells are materials that can be used as fertilizer encapsulation. This study aimed to compare the effects of nano zeolite and crab shells for encapsulation of nitrogen- potassium fertilizers tested on Entisols and Inceptisols soil on the growth and yield of shallots. The research method used a completely randomized design with three factors. The factors were soil type (Entisol and Inceptisol), coating materials (nano-zeolite and nano-crab shell), and NK fertilizer doses (125:50, 250:100, 375:150, and 500:200). The variables observed include initial soil physical and chemical properties, nanoparticle characterization, growth and yield, and agronomic efficiency. Nanoparticles were characterized using SEM and analyzed using ImageJ. The data collected were tested by ANOVA and Tukey. The ball milling method succeeded in producing 91.41% zeolite and 97.50% nano-sized crab shells. Plant height showed that using crab shells as fertilizer encapsulation with a dose of 125:50 gave better results. The yield of crab shells as encapsulation with a dose of 250:100 in inceptisols was better than that in entisols, but the highest agronomic efficiency (EA) was obtained in zeolite treatment as fertilizer encapsulation with a dose of 125:50.